PREVALENCE OF COLOR BLINDNESS IN ELEMENTARY SCHOOL-AGE CHILDREN PATIENTS AT KUTIME HEALTH CENTER, TOLIKARA DISTRICT, PAPUA PEGUNUNGAN: Oral Presentation - Observational Study - General practitioner - Ferdiansyah, Muhammad; Lovita, Audra; Daeli, Rahmat P. (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesColor blindness is a genetic disorder in the form of an inability or decreased ability to see colordifferences. Incidents of ignorance are widely reported in aspects of everyday life, such as in thelearning process, further education, and career determination. Causing disappointment in children'saspirations because it was not detected early. MethodsThis research is descriptive with cross-sectional design and total sampling technique. The sample forthis study were all pediatric patients aged 6-12 years who went to the Kutime Health Center whowere familiar with numbers and were carried out from June to December 2022. The method used apseudoisochromatic plate (Ishihara). ResultsThere were 105 children who participated in the study, while only 55 children met the inclusioncriteria. Of these, there were 32 boys (58.1%) and 23 girls (41.8%). The number of cases of colorblindness in children who went to the Kutime Health Center was 1 child (1.85%). Color blindpatients were boys (3.2%), there were no color blind girls in this study (0%). ConclusionThe prevalence rate of color blindness in the Kutime Health Center (1.85%) is still above that inPapua Province (1.39%) and nationally (0.7%). Color blindness affects more men than women,especially anyone with family history of color blindness. This research invites early detection so thatthey understand about the child's condition, the aspirations children instill can be accommodatedearlier so that there will be no disappointment regarding the choice of further education or theirfuture career.